2021
DOI: 10.1007/s10389-021-01679-8
|View full text |Cite
|
Sign up to set email alerts
|

Research priority setting in obesity: a systematic review

Abstract: Aim Obesity research priority setting, if conducted to a high standard, can help promote policy-relevant and efficient research. Therefore, there is a need to identify existing research priority setting studies conducted in the topic area of obesity and to determine the extent to which they followed good practice principles for research priority setting. Method Studies examining research priority setting in obesity were identified through searching the MED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…27 However, holding consensus groups with underrepresented Black and minority ethnic individuals and professionals together may advantage professionals, leading to the disengagement of disadvantaged groups that are underrepresented in research priority setting. 28,29 Although research prioritization exercises in obesity do exist, 30 no research could be found identifying the obesity research priorities of PW or South Asian women more generally. A research priority exercise involving South Asian children, young people and their families sought to prioritize health topics requiring more research according to this population.…”
Section: Coproducing Research Agendas With Ethnic Minority Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 However, holding consensus groups with underrepresented Black and minority ethnic individuals and professionals together may advantage professionals, leading to the disengagement of disadvantaged groups that are underrepresented in research priority setting. 28,29 Although research prioritization exercises in obesity do exist, 30 no research could be found identifying the obesity research priorities of PW or South Asian women more generally. A research priority exercise involving South Asian children, young people and their families sought to prioritize health topics requiring more research according to this population.…”
Section: Coproducing Research Agendas With Ethnic Minority Populationsmentioning
confidence: 99%
“…Although research prioritization exercises in obesity do exist, 30 no research could be found identifying the obesity research priorities of PW or South Asian women more generally. A research priority exercise involving South Asian children, young people and their families sought to prioritize health topics requiring more research according to this population 31 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, research questions that are pertinent to people may be overlooked or undervalued, 28 further marginalizing vulnerable groups. South Asian populations are underrepresented in health research, 29 and there is no evidence of research prioritization exercises conducted with any South Asian groups in the area of obesity 30 . Therefore, the research question that this study aimed to address was follows: What are the obesity concerns of Pakistani women living in deprived inner‐city areas of Bradford?…”
Section: Introductionmentioning
confidence: 99%
“…In doing so, our study may highlight potential unmet pain-related healthcare needs and help inform the development and integration of targeted pain management strategies within WMSs with the aim of improving pain outcomes as well as weight loss, health status and quality of life. Pain management appears not to be a priority within obesity research at present 113 even though people living with obesity have reported that musculoskeletal pain limits physical activity and social participation. 114 …”
Section: Discussionmentioning
confidence: 99%